Effect of Planar Impact Modeling on the Pounding Response of Base-Isolated Buildings - Mavronicola, Eftychia A.; Polycarpou, Panayiotis C.; Komodromos, Petros (Frontiers in Built Environment, 2016)
During strong earthquake excitations, base-isolated buildings may collide, either with the surrounding moat wall or with adjacent buildings if the available clearance is exceeded. This undesirable possibility has been recently investigated by several researchers, adopting various types of force-based impact models. Evidently, an important issue that arises regarding such numerical studies is the way of taking into account potential impacts. This paper parametrically investigates the effects of impact modeling characteristics on the computed overall peak response of a base-isolated building that experiences structural pounding. Specifically, the Kelvin-Voigt impact model and various other modifications of this linear viscoelastic impact model are considered in the conducted analyses. In order to efficiently conduct this investigation a specially developed software is utilized. The results indicate that the excitation’s and isolator’s characteristics do not significantly influence the variation of the normalized peak response of the superstructure. In contrast, the impact parameters can have a significant effect on the superstructures’ peak accelerations with overestimations up to 70%. In general, the normalized peak response ratios of the inter-story drifts tend to increase as the available seismic gap clearance and the coefficient of restitution decrease, although the magnitude of the deviations is within 5%, which can be considered insignificant.